A Functional N-terminal Domain in C/EBPβ-LAP* is Required for Interacting with SWI/SNF and to Repress Ric-8B Gene Transcription in Osteoblasts - Aguilar, Rodrigo (2014)
The chromatin remodeling complex SWI/SNF and the transcription factor C/EBPβ play critical roles in osteoblastic cells as they jointly control transcription of a number of bone-related target genes. The largest C/EBPβ isoform, LAP*, possesses a short additional N-terminal domain that has been proposed to mediate the interaction of this factor with SWI/SNF in myeloid cells. Here we examine the requirement of a functional N-terminus in C/EBPβ-LAP* for binding SWI/SNF and for recruiting this complex to the Ric-8B gene to mediate transcriptional repression. We find that both C/EBPβ-LAP* and SWI/SNF simultaneously bind to the Ric-8B promoter in differentiating osteoblasts that repress Ric-8B expression. This decreased expression of Ric-8B is not accompanied by significant changes in histone acetylation at the Ric-8B gene promoter sequence. A single aminoacid change at the C/EBPβ-LAP* N-terminus (R3L) that inhibits C/EBPβ-LAP*-SWI/SNF interaction, also prevents SWI/SNF recruitment to the Ric-8B promoter as well as C/EBPβ-LAP*-dependent repression of the Ric-8B gene. Inducible expression of the C/EBPβ-LAP*R3L protein in stably transfected osteoblastic cells demonstrates that this mutant protein binds to C/EBPβ-LAP*-target promoters and competes with the endogenous C/EBPβ factor. Together our results indicate that a functional N-terminus in C/EBPβ-LAP* is required for interacting with SWI/SNF and for Ric-8B gene repression in osteoblasts.